The impact of COVID-19 pandemic on hand hygiene compliance of healthcare workers in a tertiary hospital in East China - Zhang, Xing; Ma, Yonghui; Kong, Li; Li, Yusen; Wang, Juan; Li, Ning; Xia, Yujie; Wang, Peng; Zhang, Min; Liu, Lili; Zhang, Dingding; Wen, Luhan; et al. (Frontiers in Medicine, 2023)
Introduction Hand hygiene is a cost-effective measure to reduce healthcare-associated infections (HAIs) in healthcare facilities. The impact of the coronavirus disease 2019 (COVID-19) pandemic on hand hygiene performance (HHP) provided evidence for targeted hand hygiene intervention measures. Methods This study evaluated the HHP rate in a tertiary hospital before and after the COVID-19 outbreak. HHP was checked by infection control doctors or nurses every day, and they inputted the HHP rate to the full-time infection control staff every week. A random examination of HHP was conducted by a confidential worker every month. The HHP of healthcare workers (HCWs) was monitored in the outpatient department, inpatient ward, and operating room from January 2017 to October 2022. The influence of COVID-19 prevention and control strategies on HHP was elucidated by analyzing the results of HHP during the study period. Results The average HHP rate of HCWs was 86.11% from January 2017 to October 2022. The HHP rate of HCWs after the COVID-19 pandemic was statistically significantly higher than that before the pandemic (P < 0.001). The HHP rate was the highest (93.01%) in September 2022 when the local epidemic occurred. Among the different occupation categories, medical technicians showed the highest HHP rate (89.10%). The HHP rate was the highest after contact with body fluids or blood of patients (94.47%). Conclusion The HHP rate of HCWs in our hospital showed an increasing trend in the recent 6 years, especially during the COVID-19 pandemic, and the increase was most obvious during the local epidemic.